Predictors of psychological outcomes in a longitudinal study of Latina breast cancer survivors. Issue 11 (1st November 2016) - Yanez, Betina; Maggard Gibbons, Melinda; Moreno, Patricia I.; Jorge, Alexandra; Stanton, Annette L.
Abstract : Objective: This study sought to investigate the unique contributions of socio-ecological, cultural and cancer treatment-related factors in predicting depressive symptoms and cancer-specific distress among Latinas. Design: Participants were 140 English or Spanish-speaking Latinas ( M age  = 50.6) with non-metastatic breast cancer who were assessed within two years of diagnosis (Time 1) and three months later (Time 2). Main Measures: Hierarchical regression analyses identified predictors of depressive symptoms and cancer-specific distress at Time 1 and 2. Results: Most women scored above the clinical cut-offs for depressive symptoms and cancer-specific distress. After adjusting for socio-ecological factors, greater Latino enculturation, measured by Latino ethnic identity, was significantly associated with greater cancer-specific distress at Time 1 ( β  = .20, p  < .05). A significant interaction ( p  < .01) revealed that among women high on Latino identity, lower English language use was associated with more cancer-specific distress than higher English language use. After adjusting for socio-ecological factors, greater satisfaction with surgical treatment predicted improved depressive symptoms and cancer-specific distress across time ( β s range from −.31 to −.18, p s  < .01). Conclusions: Findings elucidate the complex relationship between culture and psychological outcomes in the breast cancer context and suggest that treatment satisfaction might be an important intervention target for Latinas.